Singular perception, multiple perspectives through we: constructing intersubjective meaning in English and German - Whitt, Richard J. (John Benjamins, 2014)
This paper presents the results of a corpus-based investigation of the role of the first-person plural pronoun in the construction of intersubjective meaning among evidential perception verbs in written and spoken English and German (mainly written). Whereas the first-person singular pronoun only signifies that the evidence rests solely with the speaker/writer, the first-person plural pronoun allows a much wider range of intersubjective meanings concerning the nature of the evidence. It is also shown how English and German perception verbs express intersubjective evidential meaning in a number of different complementation patterns, how the type of this meaning is often linked to these patterns, and how the use of the first-person plural pronoun can vary among and within these constructions.